Optimization of PMU Location and Communications in a Power Grid - Almeida, Luis (2020)
Phasor Measurement Units (PMU) are specific equipment that measure phasors, magnitude and frequency of voltage and current in key points of a power grid, allowing for a more effective management of network assets. We start by presenting some formulations for the problem of determining the location to minimize the number of PMUs installed, ensuring that all buses (nodes of the power grid) are visible by at least one PMU. The formulations take also into account the existence of Zero Injection Buses (ZIBs) and the requirement of (N-1) redundancy to ensure that critical buses (e.g. buses with a generator) can be observed by at least two PMUs. This guarantees, in case one out of N installed PMUs fails, all critical buses are still observable. We assume that the communications network topology follows the topology of the power grid. With the goal to protect the communication infrastructure against failures and natural disasters, we propose models that minimize the number of Shared Risk Link Groups (SRLGs) and links in the path pair of each PMU to a pair of Phasor Data Concentrators (PDCs). We then modify the formulation of the PMU location problem to improve the resilience of the communication between the PMUs and the PDCs, namely by avoiding to place PMUs in buses of degree one and also by penalizing the placement of PMUs in buses that will result in path pairs to the PDCs which are not SRLG-disjoint. Results are presented to illustrate the impact of the modified PMU location model on the resilience of the communication network.